Bimetallic Oriented (Au/Cu2O) vs. Monometallic 1.1.1 Au (0) or 2.0.0 Cu2O Graphene‐Supported Nanoplatelets as Very Efficient Catalysts for Michael and Henry Additions. Issue 44 (26th November 2018) - Simion, Andrada; Candu, Natalia; Coman, Simona M.; Primo, Ana; Esteve‐Adell, Ivan; Michelet, Véronique; Parvulescu, Vasile I.; Garcia, Hermenegildo
Abstract : Michael and Henry addition reactions have been investigated using mono (Au and Cu2 O ) and bimetallic nanoplatelets (Au /Cu2 O ) grafted onto few‐layers graphene ( fl‐G ) films as heterogeneous catalysts by comparison with homogeneous NaOH and K2 CO3 ones. In the presence of the heterogeneous catalysts, these reactions occurred in the absence of any extrinsic (NaOH and K2 CO3 ) base with turnover numbers (TONs) at least four orders of magnitude higher. While the homogeneous catalysts provided TONs close to the unity forAu /Cu2 O/fl ‐ G this was of the order of 10 7 . These reactions also occurred with a very good selectivity to the targeted products. These performances are in line with the basicity of these catalysts demonstrated from CO2 chemisorption measurements. The effect of the nanosize and the interaction of the nanoparticles with the graphene are also important to achieve this high activity. Abstract : Michael and Henry addition reactions have been investigated using mono (Au / fl ‐G and Cu2 O/fl ‐G) and bimetallic nanoplatelets (Au /Cu2 O/fl ‐G) grafted onto few‐layers graphene films as heterogeneous catalysts. These reactions occurred in the absence of any extrinsic base with TONs at least four orders of magnitude higher.